Multidrug Resistant Epididymitis Progressing to Testicular Infarct and Orchiectomy - Nicholas J. Farber; Rick C. Slater; Jodi K. Maranchie (Case Reports in Urology)
Global testicular infarction is a rare sequela of infectious epididymitis, with few reports in the urologic literature since the introduction of fluoroquinolones in the late 1980s. Ischemia occurs secondary to inflammation and edema of the spermatic cord with compression of arterial flow. We report a case of multidrug resistant epididymitis following prostate biopsy that progressed to global testicular infarction requiring orchiectomy. This case highlights the fact that epididymitis does not always follow an indolent pathway to resolution. Progression of pain should prompt early imaging and intervention. It further highlights the potential urologic consequences of the rising prevalence of multidrug resistant bowel flora in the United States, which will increasingly influence the management of presumed uncomplicated epididymitis, whether being primary or postprocedural.